Interaction between two neighboring circular holes in a prestretched simply supported orthotropic strip under bending - Akbarov, S. D.; Yahnioglu, N.; Yesil, U. Babuscu (SPRINGER, 2008)
In this work, the influence of initial stretching of a simply supported plate-strip containing two circular holes on the stress concentration around the holes caused by bending of the strip is examined using the finite-element method. The mathematical formulation of the corresponding boundary-value problem is presented within the frame work of the three-dimensional linearized theory of elasticity (TDLTE) under a plane strain state. The material of the plate-strip is linearly elastic, homogeneous, and orthotropic. The numerical results obtained in investigating the influence of the initial stretching and the location of holes on the stress concentration are presented. In particular, it is established that the initial stretching significantly decreases the stress concentration at some characteristic points on the contour of the holes.
Keywords: initial stretching force; stress concentration; circular hole; plate-strip; orthotropic material; DEFORMATION; STRESS; SHELLS; Mechanics; Materials Science; Polymer Science